Addressing Interconnectedness : Concepts and Prudential Tools - Arregui, Nicolas (IMF Working Papers; Working Paper, 2013)
This paper reviews tools used to identify and measure interconnectedness and raises the awareness of policymakers as to potential cross-sectional implications of prudential tools aimed at controlling interconnectedness. The paper examines two sets of tools-developed at the IMF and externally-to identify the implications of interconnectedness in systemic risk and how these tools have been applied in IMF surveillance. The paper then proposes a preliminary framework to analyze some key internationally-agreed-upon and national prudential tools and finds that while many prudential tools are effective in reducing interconnectedness, the interaction among these tools is far less clear cut.